Revisión de la Familia Ropalomeridae (Diptera) en México - Ramírez García, Enrique; Hernández Ortiz, Vicente (Instituto de Ecología, A.C., 1994)
A taxonomic revisión of the family Ropalomeridae is presented, based on the analysis of specimens from 14 States of México. R. latiforceps sp. nov. is described with specimens from México and Panamo, R. xanthops Williston is synonymized with Ropalomera femorata (Fabricius), and Lenkokroeberia chryserea Prado is recorded by the first time for the country. In addition, we provide new data on the distribution of Willistoniella pleuropunctata (Wiedemann), Kroeberia fuliginosa Lindner, and Mexicoa mexicana Steyskal. Distinguishing characters for all known genera and species are keyed and illustrated.